2021
DOI: 10.1186/s12967-021-03005-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a score to predict mortality in ICU patients with sepsis: a multicenter retrospective study

Abstract: Background Early and accurate identification of septic patients at high risk for ICU mortality can help clinicians make optimal clinical decisions and improve the patients’ outcomes. This study aimed to develop and validate (internally and externally) a mortality prediction score for sepsis following admission in the ICU. Methods We extracted data retrospectively regarding adult septic patients from one teaching hospital in Wenzhou, China and a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In this study, we compared the impact of different criteria for sepsis diagnosis on sepsis frequencies and functional and survival outcomes in a cohort of 270 patients with an SAH. By choosing an SAH as the underlying condition of the study population, two important prerequisites for studies on sepsis criteria could be established [17,[20][21][22]: homogeneity in the underlying disease within the study population and development of infectious complications under full surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we compared the impact of different criteria for sepsis diagnosis on sepsis frequencies and functional and survival outcomes in a cohort of 270 patients with an SAH. By choosing an SAH as the underlying condition of the study population, two important prerequisites for studies on sepsis criteria could be established [17,[20][21][22]: homogeneity in the underlying disease within the study population and development of infectious complications under full surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…When studying sepsis criteria, two factors were identified as systematic weaknesses: first, the heterogeneity in the underlying illnesses of patients [20,21], and second, the presence of septic signs already on admission in general ICU populations, with the sepsis onset preceding the observation window of the ICU electronic health records (EHR) [17,22]. These obstacles were absent in the here analyzed SAH cohort.…”
Section: Introductionmentioning
confidence: 99%
“…These patients have an excessive depletion of albumin as a result of a large number of inflammatory factors in the body, leading to a negative nitrogen balance, tissue hypoxia, and impaired microcirculation, thereby resulting in increased capillary permeability and a further decrease in albumin level. A previous study demonstrated that low albumin level was an effective predictor of mortality in ICU septic patients [ 33 ]. Our study determined that serum albumin (27.8, 25.10-31.30 vs. 32.60, 29.50-35.90) was significantly lower in S-AKI patients than in non-AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, those complex processes may be at risk of some complications, such as subcutaneous hematoma and pseudo-aneurysm after blood sampling and time spent of at least 6 h with higher cost. In addition, the greatest weakness is that from this scoring system, the prediction of sepsis and its prognosis is not feasible [ 21 ]. To compensate for this, molecular biomarkers as a non-cellular source have been introduced as early prodiagnostic markers for human sepsis, which have overcome the drawbacks of the scoring systems [ 22 ].…”
Section: Discussionmentioning
confidence: 99%